Targeting Toxoplasma gondii CPSF3 as a new approach to control toxoplasmosis. Issue 3 (1st February 2017) - Palencia, Andrés; Bougdour, Alexandre; Brenier‐Pinchart, Marie‐Pierre; Touquet, Bastien; Bertini, Rose‐Laurence; Sensi, Cristina; Gay, Gabrielle; Vollaire, Julien; Josserand, Véronique; Easom, Eric; Freund, Yvonne R; Pelloux, Hervé; et al.
Abstract: Toxoplasma gondii is an important food and waterborne pathogen causing toxoplasmosis, a potentially severe disease in immunocompromised or congenitally infected humans. Available therapeutic agents are limited by suboptimal efficacy and frequent side effects that can lead to treatment discontinuation. Here we report that the benzoxaborole AN3661 had potent in vitro activity against T. gondii . Parasites selected to be resistant to AN3661 had mutations in TgCPSF3, which encodes a homologue of cleavage and polyadenylation specificity factor subunit 3 (CPSF‐73 or CPSF3), an endonuclease involved in mRNA processing in eukaryotes. Point mutations in TgCPSF3 introduced into wild‐type parasites using the CRISPR/Cas9 system recapitulated the resistance phenotype. Importantly, mice infected with T. gondii and treated orally with AN3661 did not develop any apparent illness, while untreated controls had lethal infections. Therefore, Tg CPSF3 is a promising novel target of T. gondii that provides an opportunity for the development of anti‐parasitic drugs. Synopsis: Benzoxaboroles are boron‐containing compounds effective against a wide range of infectious pathogens. The benzoxaborole AN3661 is a novel drug candidate against acute toxoplasmosis. The compound blocks an unprecedented target of Toxoplasma, the endonuclease CPSF3 that cleaves 3′‐mRNAs in eukaryotes. AN3661 inhibits Toxoplasma growth in vitro at low micromolar concentrations, with potency comparable to that of the clinically relevant drug pyrimethamine. AN3661 orally administered to mice controls otherwise lethal infections with comparable efficacy to sulfadiazine, the standard of care to treat toxoplasmosis. Mice treated with AN3661 developed protective immunity to subsequent Toxoplasma infections. Forward genetics and CRISPR/Cas9 editing validated CPSF3 as the main target of AN3661 in Toxoplasma . Structural modelling allowed to place the resistant mutations at the Toxoplasma CPSF3 catalytic site and to identify the putative binding site of AN3661. Abstract : Benzoxaboroles are boron‐containing compounds effective against a wide range of infectious pathogens. The benzoxaborole AN3661 is a novel drug candidate against acute toxoplasmosis. The compound blocks an unprecedented target of Toxoplasma, the endonuclease CPSF3 that cleaves 3′‐mRNAs in eukaryotes.